2017
DOI: 10.1371/journal.pgen.1006750
|View full text |Cite
|
Sign up to set email alerts
|

TCF21 and the environmental sensor aryl-hydrocarbon receptor cooperate to activate a pro-inflammatory gene expression program in coronary artery smooth muscle cells

Abstract: Both environmental factors and genetic loci have been associated with coronary artery disease (CAD), however gene-gene and gene-environment interactions that might identify molecular mechanisms of risk are not easily studied by human genetic approaches. We have previously identified the transcription factor TCF21 as the causal CAD gene at 6q23.2 and characterized its downstream transcriptional network that is enriched for CAD GWAS genes. Here we investigate the hypothesis that TCF21 interacts with a downstream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 61 publications
(82 reference statements)
1
55
0
Order By: Relevance
“…[15][16][17][18] In disease, Tcf21 is reported to function as a tumor suppressor and loss of Tcf21 expression and/or methylation of its promoter have been identified in a variety of lung and urogenital tumors. 19,20 In other studies, Tcf21 has been linked to coronary artery disease, 21,22 podocyte differentiation, diabetic kidney disease, 23 and changes in adipose phenotype. 24 In the kidney, previous work has shown that Tcf21 null mutant mice are born with severely hypoplastic kidneys, and that although Tcf21 is exclusively expressed in the mesenchyme, in its absence, major defects in UB epithelial differentiation and branching are observed.…”
Section: Discussionmentioning
confidence: 94%
“…[15][16][17][18] In disease, Tcf21 is reported to function as a tumor suppressor and loss of Tcf21 expression and/or methylation of its promoter have been identified in a variety of lung and urogenital tumors. 19,20 In other studies, Tcf21 has been linked to coronary artery disease, 21,22 podocyte differentiation, diabetic kidney disease, 23 and changes in adipose phenotype. 24 In the kidney, previous work has shown that Tcf21 null mutant mice are born with severely hypoplastic kidneys, and that although Tcf21 is exclusively expressed in the mesenchyme, in its absence, major defects in UB epithelial differentiation and branching are observed.…”
Section: Discussionmentioning
confidence: 94%
“…In our previous work, we have shown that TCF21, a highly replicated gene associated with CAD, interacts closely with AHR. 9 We also found that TCF21 plays a central role in regulating SMC phenotype and in modulating SMC phenotypic modulation during atherosclerosis. [10][11][12] However, the role of the AHR pathway in regulating SMC phenotypic modulation in atherosclerotic disease is not well understood.…”
Section: Introductionmentioning
confidence: 60%
“…We have previously shown that TCF21 represents a potent factor in HCASMC that can shape the future of this cell type during embryogenesis and athero-development (Kim et al 2017;Nurnberg et al 2015;Sazonova et al 2015;Wirka et al 2019). One of the most important protective mechanisms during lesion formation and expansion is the phenotypic modulation of HCASMC.…”
Section: Discussionmentioning
confidence: 99%